MAP17, a ROS-dependent oncogene - Carnero, Amancio (Frontiers in Oncology, 2012)
MAP17 is a small 17 kDa non-glycosylated membrane protein previously identified as being overexpressed in carcinomas. Breast tumor cells that overexpress MAP17 show an increased tumoral phenotype with enhanced proliferative capabilities both in the presence or the absence of contact inhibition, decreased apoptotic sensitivity and increased migration. MAP17-expressing clones also grow better in nude mice. The increased malignant cell behavior induced by MAP17 is associated with an increase in reactive oxygen species, ROS, production, and the treatment of MAP17-expressing cells with antioxidants results in a reduction in the tumorigenic properties of these cells. The MAP17-dependent increase in ROS and tumorigenesis relies on its PDZ-binding domain because disruption of this sequence by point mutations abolishes the ability of MAP17 to enhance ROS production and tumorigenesis. MAP17 is overexpressed in a great variety of human carcinomas, including breast tumors. Immunohistochemical analysis of MAP17 during cancer progression demonstrates that overexpression of the protein strongly correlates with tumoral progression. Generalized MAP17 overexpression in human carcinomas indicates that MAP17 can be a good marker for tumorigenesis and, especially, for malignant progression.